THE ROLE OF THE GOVERNMENT IN THE EFFORT OF MANGROVE FOREST CONSERVATION IN THE COASTAL AREA OF TARAKAN CITY, NORTH KALIMANTAN PROVINCE - Kartini Maharani Abdul; Syaini Syaini (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2021)
The city of Tarakan has a very wide mangrove forest, as for the phenomena and problems in mangrove conservation, namely the irresponsibility of the community who transfers land functions for personal purposes. Some of the mangrove areas are aquaculture areas by the community and there are residential areas in the mangrove area. The purpose of this study is to analyze and determine the aspects that influence the role of the government in its efforts to preserve mangrove forests in the coastal area of Tarakan City, North Kalimantan Province. The method used is descriptive qualitative. The research was carried out in the City of Tarakan and the City of Tanjung Selor, the Province of North Kalimantan, for data collection the authors visited the Forestry Service of the Province of North Kalimantan, the KPH of the City of Tarakan and the BLH of the City of Tarakan. Data were collected through direct observation, interviews and documentation. This research resulted in the role of the government as a facilitator, regulator, catalyst and efforts to preserve the mangrove forest of Tarakan City, namely mangrove conservation areas, mangrove replanting, restoration/rehabilitation of mangrove areas, public education and factors that have an influence including the availability of facilities and infrastructure, budget availability, partnerships and community participation. The conclusion shows the role of the government in its efforts to preserve mangrove forests in the coastal area of Tarakan City as much as possible, but there are still obstacles in the field that are in direct contact with people who carry out activities around the mangrove area and the need for budget fulfillment for the implementation of mangrove forest rehabilitation.